Identification of fertility zones and assessment of potential crop yield based on biological farming approaches - Natalia V. Ovcharova; Marina M. Silantieva; Vladimir I. Belyaev; Yuri A. Gulyanov; Lyudmila V. Sokolova; Tatiana G. Plutalova; Irina Yu. Botvich; Dmitriy V. Emelyanov; Nikolai P. Belov (Acta Biologica Sibirica, 2023)
The biopotential productivity of agricultural land, along with the preservation of the biological diversity of adjacent landscapes through the development and implementation of high-tech agricultural technologies, is of critical concern in the current climatic changes and urbanization. The article reports the results of an integrated approach to the development of task maps for differentiated seeding and mineral fertilization using various tillage techniques (conventional subsurface tillage and no-till) in the experimental fields of two farms in the Altai Krai. The farms are located in the Aleiskaya soil and climate zone. The soils in the experimental fields showed a very low nitrate nitrogen content, which did not exceed 3.0 mg/kg of soil in the upper (0–10 cm) layer and 2.7 mg/kg of soil in the 10–20 cm layer. We revealed that one of the main indicators that affects soil fertility is the spatial differentiation of the humus content of humus and the main nutrients. Soil moisture was found to vary at different soil depths (11.4–25.3%), indicating a significant effect of soil fertility grades and autumn tillage techniques on moisture accumulation and distribution at different soil depths in spring, and consequently on the vegetation soil moisture regime and crop yield.